Youth leadership and community mobilization for sustainable rural development: a phenomenological study in indonesia - Desika Putri Mardiani; Gunarti Dwi Lestari; Nunuk Hariyati; Rofik Jalal Rosyanafi; Ima Widiyanah; Tri 'Ulya Qodriyati; Clara Hetty Primasari; Achmad Irfandi (Jurnal Konseling dan Pendidikan, 2025)
Amidst rapid urbanization and the large-scale migration of young people from rural areas to cities and abroad, a group of rural residents continues to demonstrate a strong commitment to staying in their villages and actively contributing to local development. This study aims to: 1) describe the various contributions of rural youth who assume leadership roles in mobilizing communities to improve collective welfare; 2) analyze youth behavior in building community networks that support sustainable livelihoods; 3) identify key factors influencing rural youth leadership in village development. The research employed a qualitative method with a phenomenological approach to capture the lived experiences of rural youth leaders. Data were collected through in-depth interviews, supported by observation and documentation. Data analysis followed the Miles and Huberman interactive model, including data condensation, data display, and conclusion drawing and verification. The findings reveal that rural youth function as agents of community-based initiatives and the strengthening of social competitiveness. Youth leadership revitalizes mutual cooperation, social solidarity, and local independence, enabling communities to respond adaptively to socio-economic challenges. The novelty of this study lies in its focus on youth-led collective leadership as a sustainable alternative to rural out-migration, linking grassroots youth agency with the achievement of the Sustainable Development Goals (SDGs). Practically, the findings offer a replicable strategy for policymakers and rural development practitioners to empower youth as key drivers of inclusive and sustainable village development.